Enhancing Higher Order Thinking Skills through Active Learning in Islamic Religious Education at a Vocational High School in Indonesia - Muhammad Arifin Rahmanto; Bunyamin Bunyamin; Sintha Wahjusaputri (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the implementation of Active Learning strategies to enhance Higher Order Thinking Skills (HOTS) in Islamic Religious Education (PAI) at a vocational high school in Indonesia. The research responds to the challenge of improving students' analytical, evaluative, and creative abilities in a subject often taught through passive methods. A qualitative descriptive approach was used, involving structured interviews, classroom observations, and document analysis. Participants included 12 students, two PAI teachers, and one vice principal at SMKN 3 South Tangerang. Data were analyzed using an interactive model that incorporated reduction, display, and verification processes. The study found that Active Learning strategies—such as problem-based learning, project-based learning, think-pair-share, and role-play—were effectively integrated into PAI instruction. These methods were supported by two key approaches: the administrative mode (lesson planning, classroom management, and HOTS-based assessments) and the internalization mode (reflection, values education, and student-centered expression). As a result, students showed notable improvement in HOTS indicators: analysis (C4) increased from 62% to 78%, evaluation (C5) from 58% to 74%, and creation (C6) from 55% to 71%. Active Learning in PAI not only improved cognitive outcomes but also fostered reflective and ethical engagement with Islamic teachings. The findings suggest that structured yet flexible pedagogical models can make religious education more participatory, contextual, and relevant to real-world challenges, particularly in vocational school settings.